Case Report: IBD-like colitis following CAR T cell therapy for diffuse large B cell lymphoma - Zundler, Sebastian; Vitali, Francesco; Kharboutli, Soraya; Völkl, Simon; Polifka, Iris; Mackensen, Andreas; Atreya, Raja; Neurath, Markus F.; Mougiakakos, Dimitrios (Frontiers in Oncology, 2023)
Chimeric antigen receptor (CAR) T cell therapy has become a new mainstay in the treatment of several hematologic malignancies, but the spectrum of associated complications is still incompletely defined. Here, we report the case of a 70-year-old female patient treated with tisagenlecleucel for diffuse large B cell lymphoma (DLBCL), who developed chronic diarrhea with characteristics of inflammatory bowel disease (IBD)-like colitis. CAR-T cells were substantially enriched in the colon lamina propria and other diagnoses were ruled out. Thus, we conclude that IBD-like colitis in this patient was associated to CAR-T cell therapy and needs to be considered as a rare potential complication.